Sudden sustained monomorphic ventricular tachycardia in a previously healthy adult with many causes for it, but which is the correct one? - Jović, Zoran; Opančina, Miljan; Mladenović, Zorica; Djurić, Predrag; Djurić, Ivica; Marić Kocijančić, Jelena; Djenić, Nemanja; Opančina, Valentina; Obradović, Slobodan (Vojnosanitetski pregled, 2024)
Introduction. Sustained monomorphic ventricular tachycardia (VT) – SMVT is a rare, underdiagnosed pathology with a very poor prognosis. Along with ventricular fibrillation, SMVT is responsible for nearly all of the arrhythmic sudden cardiac deaths (SCD). The most common cause of VT is ischemic heart disease, but there are many other reasons, among which are arrhythmogenic right ventricular cardiomyopathy (ARVD) and myocardial bridging phenomenon. Treatment options include a hybrid approach consisting of antiarrhythmic drugs, catheter ablation, and implantable cardioverter defibrillators (ICD). Case report. We present a case of a 46-year-old man, a military officer, who experienced chest pain, palpitations, and nausea during regular physical activity at home. Due to the symptoms described, he was examined immediately and diagnosed with SMVT. Shortly after the diagnosis, he lost consciousness and was successfully resuscitated. A complete non-invasive and invasive cardiology examination was performed. It revealed that the patient had stable coronary disease and a muscle bridge on the left anterior descending artery. An ARVD was suspected after transthoracic echocardiography and heart magnetic resonance imaging. Genetic testing for ARVD was negative, but according to the Heart Rhythm Society expert consensus criteria, we had enough for a definitive diagnosis. The patient was hospitalized for ten days and treated with drugs without recurring VT or other disorders. We implanted an implantable loop recorder before the discharge and monitored the heart rhythm for one year. During a three-year follow-up, all of his electrocardiographic findings presented sinus rhythm without heart rhythm disorders. Conclusion. Sudden SMVT is the most common cause of SCD. It is of inestimable importance to carry out a detailed examination and determine the immediate cause of the arrhythmia and the right therapy, which, for these patients, is a life-saving form of treatment. Therapy includes medications, electrophysiology or ICD, or a combination of these treatment approaches.
Keywords: cardiomyopathies; coronary disease; defibrillators, implantable; diagnosis; magnetic resonance imaging; myocardial bridging; tachycardia, ventricular; ultrasonography